SMART SOCKS SYSTEM AS AN EQUIPMENT TO ANALYZE TEMPORAL PARAMETERS OF HUMAN GAIT AND RUNNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The aim of present study was to demonstrate usability of the recently developed “Smart Socks” System for analysis of locomotion temporal parameters. Smart socks system exploits pressure sensors which can be knitted directly in the garment, thus providing minimal discomfort for user. Two types of locomotion were analysed: walking and running. Experienced athletes took part in the experiment to perform movements in the controlled conditions in laboratory. The research demonstrated that temporal accuracy of Smart Sock system is acceptable for practical purposes. Data, provided by the system could distinguish heel strike and non-heel strike run and walk modes. More data is required for deeper analysis and interpretation of obtained temporal parameters and for development of recommendations for athletes and coaches.